Student Perceptions About Using Google Classroom and Its Effect on Student Learning Motivation - Siska Mulyana; Rr Srikartikowati; Hendripides Hendripides (STAI Hubbulwathan Duri, 2023)
This study is based in the context of online learning, which has led to students experiencing delays in assignment completion and reduced cooperation in discussion groups. The objective of this study is to ascertain student perspectives on the utilisation of Google Classroom and to assess the impact of its use on the learning motivation of students majoring in Economics Education. The sampling technique employed was random sampling, specifically with a sample size of 53 respondents. This study employs quantitative descriptive methodologies, utilising data analysis techniques such as normality tests, linearity tests, f tests, and simple linear regression tests. The research findings indicate a statistically significant value of 147,272 4.03, demonstrating a strong correlation between the utilisation of Google Classroom and student motivation for learning. The coefficient of determination is 0.743, indicating a strong positive link. This suggests that there is a major influence.